"Caracterización geológica y descripción de las propiedades físico - químicas del depósito de caolín, ubicado en el km 5 vía Loja- Cuenca, sector Zalapa Alto, cantón y provincia de Loja". - Chicaiza Songor, Gabriela Paulina (2019)
The present research work entitled "Geological Characterization and Description of the Physical - Chemical Properties of the Deposit of Kaolin, Located at Km 5 Loja - Cuenca, Zalapa Alto Sector Route, Canton and Province of Loja" was aimed at the identification and establishment of the geological characteristics, the quality of the minerals by means of the determination of the physical - chemical properties, the chemical and mineralogical composition with the use of methodologies. It began with a detailed survey of the topography of 10 Ha of study, resulting in an irregular surface with medium hills and steep terrain with slopes from strong to very steep and a variation in height that fluctuate between 2536 m s.n.m. and 2590 m s.n.m., the geology was obtained from the description of outcrops, where it was determined that the area is constituted by reddish orange-white kaolin as the predominant material and rhyodacite tuffs belonging to the Salapa Formation. It was sampled in outcrops and pits, "Chip Panel" sampling method (wall - outcrop and base - pit), the samples were taken and analyzed in the Chemistry and Geochemistry Laboratory, Mineralogy and Petrography Laboratory from the UNL. Were made all the physical - chemical analysis characteristics using: - The Munsell Notation System (Color), - Norma-ASTM_D2216 (Humity), - Pycnometer Method - Norma-ASTM_D854 (Real Density), - "Big House Spoon" - Norma-ASTM_D423-66 Liquid and Norma limit-ASTM_D424-59 Plastic Limit, - Textural Diagram of the USDA (Texture), - Hydrometer Method (H151) - Norma INV E 124-07 (Sedimentometry), - Method of Calcination and Ignition (Organic matter), - Peachimeter (pH), and - Conductivity (Conductivity). The chemical and mineralogical composition was determined by sending the samples to the Extractive Metallurgy Laboratories, X-Ray Diffraction Laboratory of the UTPL, so that by X-ray fluorescence higher values of SiO2, Al2O3 and high content of Fe2O3 were obtained. Likewise, by means of X-ray diffraction, minerals were qualitatively and quantitatively identified, such as quartz, kaolinite and unusual minerals such as aerinite and heulandite. After completing the experimental phase and with the results obtained from physical - chemical properties, and especially the chemical - mineralogical composition, it was established that the mineral corresponding to the northeast and southwest zones according to their percentages of silica and alumina shows a higher quality with respect to the southeast area; In addition, the quality is also measured by the percentage of ferric oxide, so that the area to the southeast and northeast demonstrates a lower quality kaolin, while to the southwest of the study area is a material of first quality. In total in the kaolin deposit of the Salapa Alto neighborhood, there are reserves of 500 thousand tons, currently exploited and commercialized. The manufacture of ceramics is the main industry that can make use of this type of mineral (natural state) specifically in the manufacture of bricks and tiles. Likewise, to expand its use, it must submit test to previous treatments to maximize its properties and include it in other manufactures